Criminological Aspects of Meat Misbranding at Dhaka City in Bangladesh (Journal of Environmental Science and Natural Resources, 2017)
The ultimate goal of this study was to investigate the level of meat misbranding and adulteration from slaughterhouses, which is an indirect criminal activity according to the food law. In this study 87 slaughterhouses were selected from 30 markets in Dhaka municipal area purposively to collect data through a well-structured questionnaire. Results showed that a significant percentages of illegal activities done in slaughterhouses. Low weight given during the selling operations, mixing low quality species of meat with high quality one, low quality part of meat through hiding consumer concerns, water mixing before or after slaughter, un-hygienic practices and the level were 56.32%; 49.43%; 42.53%; 72.41% and 85.18% respectively. On the other hand, about 8.04% slaughterhouse used different types of non-meat chemical ingredients illegally to their product. Among four observed chemical sodium phosphate was used in 2.3% of slaughterhouses, nitrate & nitrite was used in 1.15% of slaughterhouses, sodium chloride was also used in 2.3% of slaughterhouses and cleaners & sanitizers was used in 3.45% of slaughterhouses. About 91.96% of slaughterhouses did not use those non meat ingredients chemical.J. Environ. Sci. & Natural Resources, 10(1): 41-44 2017